Pendampingan Program Pengembangan Ekowisata Mangrove dengan Kegiatan Konservasi Lingkungan - Khambali Khambali; Rachmaniyah Rachmaniyah; Fitri Rokhmalia (FORIKES, 2020)
Ecotourism or Nature Tourism is a tourism activity that is responsible for unspoiled areas that are managed according to natural rules, with the aim of enjoying the beauty of nature which involves elements of education, understanding and support for efforts to conserve nature and increase income and welfare. The development of ecotourism in the form of sustainable tourism villages based on community empowerment is an effort to include the role of the community in tourism village activities known as